Choices in the 11-20 game: The role of risk aversion - King King Li; Kang Rong (Games, 2018)
Arad and Rubinstein (2012, AER) proposed the 11-20 money request game as an alternative to the P beauty contest game for measuring the depth of thinking. In this paper, we show theoretically that in the Nash equilibrium of the 11-20 game players are more likely to choose high numbers if they are risk-averse rather than risk neutral. Hence, the depth of thinking measured in the 11-20 game is biased by risk aversion. Based on a lab experiment, we confirm this hypothesis empirically.
Keywords: 330; rationality; measuring depth of thinking; risk aversion; experiment